Management of Laryngopharyngeal Reflux in Asia - ENVER, NECATİ (KOREAN SOC OTORHINOLARYNGOL, 2020)
Objectives. This study was conducted to investigate the current practice of Asian otolaryngologists for laryngopharyngeal reflux (LPR). Methods. An online survey about LPR was sent to 2,000 members of Asian otolaryngological societies, and a subgroup analysis was performed between Western and Eastern Asian otolaryngologists.The survey was conducted by the Laryngopharyngeal Reflux Study Group of Young Otolaryngologists of the International Federation of Oto-rhino-laryngological Societies. Results. Among approximately 1,600 Asian otolaryngologists, 146 completed the survey (62 from Western Asian countries, 84 from Eastern Asian countries). A substantial majority (73.3%) of the otolaryngologists considered LPR and gastroesophageal reflux disease to be different diseases. The symptoms thought to be closely related to LPR were coughing after lying down, throat clearing, and globus sensation. The findings thought to be closely related to LPR were posterior commissure granulations and hypertrophy, arytenoids, and laryngeal erythema. The respondents indicated that they mostly diagnosed LPR (70%) after an empirical therapeutic trial of proton pump inhibitors (PPIs). Although multichannel intraluminal impedance-pH (MII-pH) monitoring is a useful tool for diagnosing nonacid or mixed LPR, 78% of Asian otolaryngologists never or very rarely used MII-pl I. Eastern Asian otolaryngologists more frequently used once-daily PPIs (64.3% vs. 45.2%, P=0.021), whereas Western Asian otolaryngologists preferred to use twice-daily PPIs (58.1% vs. 39.3%, P=0.025). The poor dietary habits of patients were considered to be the main reason for therapeutic failure by Asian otolaryngologists (53.8%). Only 48.6% of Asian otolaryngologists considered themselves to be adequately knowledgeable and skilled regarding LPR. Conclusion. Significant differences exist between Western and Eastern Asian otolaryngologists in the diagnosis and treatment of LPR. Future consensus statements are needed to establish diagnostic criteria and therapeutic regimens.
Keywords: Laryngopharyngeal Reflux; Otolaryngologist; Disease Management; Therapeuties; Surveys and Questionnaires; PUMP INHIBITOR THERAPY; LOW-ACID DIET; GASTROESOPHAGEAL-REFLUX; OTITIS-MEDIA; PREVALENCE; DISEASE; MANIFESTATIONS; ASSOCIATION; PREDICTORS; SYMPTOMS